2021
DOI: 10.3389/fimmu.2021.690653
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil: A Nonnegligible Predictor in COVID-19 Re-Positive Patients

Abstract: Although vaccine resources are being distributed worldwide, insufficient vaccine production remains a major obstacle to herd immunity. In such an environment, the cases of re-positive occurred frequently, and there is a big controversy regarding the cause of re-positive episodes and the infectivity of re-positive cases. In this case-control study, we tracked 39 patients diagnosed with COVID-19 from the Jiaodong Peninsula area of China, of which 7 patients tested re-positive. We compared the sex distribution, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(63 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, regarding eosinopenia, we found that at a cut-off value of more than 0.31%, 74% of patients were expected not to develop severe COVID-19, while with respect to mortality, at a cut-off value of more than 0.18%, 73% of patients were expected to survive. These findings are corroborated by current research that has emphasized both lymphopenia and eosinopenia as key markers of severity and mortality [20][21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, regarding eosinopenia, we found that at a cut-off value of more than 0.31%, 74% of patients were expected not to develop severe COVID-19, while with respect to mortality, at a cut-off value of more than 0.18%, 73% of patients were expected to survive. These findings are corroborated by current research that has emphasized both lymphopenia and eosinopenia as key markers of severity and mortality [20][21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 73%
“…In general, EVs have been used as carriers to deliver endogenous or exogenous drugs for disease treatment. Oxidative stress is an abnormal physiological phenomenon, and it is defined as “an imbalance between antioxidants and oxidants, resulting in the disruption of redox signaling and the corresponding molecular damage.” To the best of our knowledge, it is associated with nearly all diseases such as cancers ( Hayes et al, 2020 ), cardiovascular diseases ( Dubois-Deruy et al, 2020 ), aortic dissection ( Zong et al, 2021 ), atherosclerosis ( Li et al, 2021 ; Xue et al, 2021 ), COVID-19 ( Li et al, 2021 ), drug-induced injuries ( Li et al, 2021 ), and diabetes ( Zhang et al, 2020 ). The effective regulation or relief of oxidative stress can potentially prevent many diseases, and EVs play an important role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…We reported a series of delayed DH in the context of severe COVID-19 with high frequency of eosinophilia (2/3 of the patients) whereas some studies suggested that eosinopenia is associated with severe COVID-19 5 or SARS-CoV-2 reactivation. 6 Viral reactivations (especially EBV) were frequently observed in our patients. Frequent EBV reactivations were previously reported during COVID-19, with a strong association between viral load and disease severity.…”
mentioning
confidence: 74%
“…Data available on request from the authors. B. Mille, 1 S. Ingen-Housz-Oro, 2,3 N. De Prost, 4 G. Voiriot, 5 A. Soria, 6,7…”
Section: Conflict Of Interestmentioning
confidence: 99%